(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
The article is devoted to the ecology urgent issues, safety of ecosystems in Kryvyi Rih region, expediency and necessity of monitoring’s using of ecologically modiﬁed forest cultural phytocenoses.